Impact of Unintended pregnancy on HIV viral load outcomes among postpartum women living with HIV in Cape Town, South Africa: clues from postpartum adherence clubs for antiretroviral therapy trial - Mwalye, Pumulo Justine (Department of Public Health and Family Medicine, 2023)
Introduction: Postpartum women living with HIV (WLWHIV) on antiretroviral therapy (ART) are at high risk of viraemia. We examined the association between unintended pregnancy and HIV viral load (VL) at 24 months postpartum in Cape Town, South Africa. Methods: Data are from a randomised trial that compared different ART delivery modalities for postpartum women aged at least 18 years who had initiated ART during their most recent pregnancy, had a VL<400 copies/ml in the previous three months, and had no comorbidities necessitating regular clinical follow-up. Pregnancy intentions regarding the most recent pregnancy were self-reported at enrolment into the study. VL was measured at 24 months postpartum, with elevated VL defined as VL≥1000 copies/ml. Chi-squared tests and logistic regression were used to examine predictors of unintended pregnancy. The impact of unintended pregnancy on elevated VL was examined using Poisson regression models. Results: Among 411 women included in the analysis (mean age: 28.7 years, 42% married/cohabiting, 75% with a parity≥2, and 86% with a VL<50 copies/ml), 57% reported that their most recent pregnancy was unintended. Compared to women aged 18-24 years, older women had a lower relative odds of unintended pregnancy [25-28 years, adjusted odds ratio (AOR): 0.34; 95% confidence interval (CI): 0.17-0.70; 29-34 years, AOR: 0.18; CI: 0.08-0.37; and ≥35 years, AOR: 0.35; CI: 0.14-0.89]. Additionally, unintended pregnancy was associated with being unmarried/not cohabiting (AOR: 4.44; CI: 2.78-7.09) and with higher parity (compared to parity=1: parity=2, AOR: 3.47; 95% CI: 1.86-6.50; and parity≥3, AOR: 6.38; 95% CI: 3.06-13.28). VL data at 24 months postpartum were available for 89% (366/411) of participants of whom 24% had elevated VL≥1000 copies/ml. Unintended pregnancy was associated with elevated VL in unadjusted analyses [risk ratio (RR): 1.54; CI: 1.03-2.28; p=0.032]. After adjustment for maternal factors and trial allocation, the association persisted despite not reaching statistical significance (adjusted risk ratio (aRR): 1.36; CI: 0.88-2.08; p=0.158). Conclusion: Among postpartum WLWHIV in South Africa, unintended pregnancy is prevalent and could be a risk factor for elevated VL. Reproductive health counselling and support during routine care visits may reduce unintended pregnancies and its effects.